1990
DOI: 10.1093/brain/113.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Progressive Aphasia Due to Focal Cortical Atrophy

Abstract: Six patients with a slowly progressive aphasic disorder due to degenerative cortical disease are reported. The length of history varied from 18 months to 6 years. In 5 patients, there was a naming deficit, associated in 4 of these with some abnormalities in comprehension. One patient had a progressive history of reduced speech output, which was associated with an orofacial dyspraxia. All patients were studied neuropsychologically, and in addition regional cerebral metabolism was measured using position emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…19 -21 Moreover, positron emission tomography (PET) and single-photon emission computerized tomography in patients with PPA have shown restingstate deficits in cortical metabolism and blood flow in left anterior and posterior perisylvian regions. 2,[22][23][24] Although some right-sided abnormalities have been found in a few cases, the metabolic state of the right hemisphere generally has been within normal limits in these studies. Thus, resting functional imaging data have largely reflected the clinical focality of PPA.…”
mentioning
confidence: 63%
“…19 -21 Moreover, positron emission tomography (PET) and single-photon emission computerized tomography in patients with PPA have shown restingstate deficits in cortical metabolism and blood flow in left anterior and posterior perisylvian regions. 2,[22][23][24] Although some right-sided abnormalities have been found in a few cases, the metabolic state of the right hemisphere generally has been within normal limits in these studies. Thus, resting functional imaging data have largely reflected the clinical focality of PPA.…”
mentioning
confidence: 63%
“…Since the first landmark studies [40,41] 18 F-FDG-PET functional investigations have provided consistent findings of bilateral hypometabolism in temporal lobes, peaking in the TPs, and usually prevalent to the left [24,4248]. Some authors have reported an additional involvement of the basal ganglia (caudate nucleus), thalamus [42,43,45], subcallosal gyrus/orbitofrontal cortex (SCG, OFC) [24,42,44,46], insula [42,49], anterior cingulate cortex (aCG) [50], and fusiform gyrus (FFG) [24,43,44,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other degenerative dementias, attention, memory, and other cognitive functions are relatively preserved within initial phases of illness. PPA has been associated with circumscribed atrophy and functional disruption in left-hemisphere perisylvian and temporal brain regions (Chawluk et al, 1986;Tyrrell et al, 1990;Abe et al, 1997;Westbury and Bub, 1997;Sonty et al, 2003;Gorno-Tempini et al, 2004). The behavioral and structural focality of PPA make it an important model for studying the functional anatomy of language and the effects of degenerative disease on brain function.…”
Section: Introductionmentioning
confidence: 99%